Wave of the Sea Dragon - West, Tracey, 1965-; Loveridge, Matt (New York : Branches/Scholastic Inc., 2021)
Drake and the other Dragon Masters go to the island of Kapua seeking a Sea Dragon needed to help stop the evil wizard Astrid's dangerous False Life spell.
Ages 5-7.
Grades 2-3.
570L
Decoding demand: 71 (high) Semantic demand: 93 (very high) Syntactic demand: 69 (high) Structure demand: 85 (very high)
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Wizards -- Juvenile fiction; Magic -- Fiction; Adventure and adventurers -- Fiction; Fantasy fiction; Action and adventure fiction